Food Plot Use by Juvenile Northern Bobwhites in East Texas - D. Scott Parsons; R. Montague Whiting Jr.; Xiangwen Liu; Donald R. Dietz (National Quail Symposium Proceedings, 2017)
We examined use of spring-summer (i.e., warm-season) food plots by northern bobwhites (Colinus virginianus) with broods using radio telemetry on a 563-ha study area in Trinity County, eastern Texas, where habitat was modified to enhance it for these birds. Bobwhites from South Texas and disjunct areas of East Texas were introduced to supplement a small, resident population. All relocated and most resident bobwhites were fitted with necklace-style transmitters. Bobwhites which produced chicks were intensively radiotracked (≥3 times/day) for ≥4 weeks or until the radio-marked parent was lost. Nine hens moved their broods to food plots within an average of 2.1 days after the eggs hatched; average distance moved was 217 m. Use of food plots by 12 broods was proportionally greater than that of native vegetation (P < 0.001). Food plots had lower quail-level foliage density (P = 0.015) and more arthropods (P < 0.001) than native vegetation. Our results demonstrate that warm-season food plots can potentially provide brood habitat for bobwhites in eastern Texas.